Quality of match for statistical matches used in the development of the Levy Institute Measure of Time and Consumption Poverty (LIMTCP) for Ghana and Tanzania - Fernando Rios-Avila (Levy Economics Institute of Bard College, 2016)
This document presents a description of the quality of match of the statistical matches used in the LIMTCP estimates prepared for Ghana and Tanzania. For Ghana, the statistical match combines the Living Standards Survey Round 6 (GLSS6) with the Ghana Time Use Survey (GTUS) 2009, and for Tanzania it combines the Household Budget Survey (THBS) 2012 with the time-use data obtained from the Integrated Labor Survey Module (ILFS) 2006. In both cases, the alignment of the two datasets is examined, after which various aspects of the match quality are described. Despite the differences in the survey years, the quality of match is high and the synthetic dataset appropriate for the time poverty analysis.
Keywords: C14; C40; D31; J22; 330; Statistical Matching; Time Use; Household Production; Poverty; LIMTCP; Ghana; Tanzania